Digital collections of cultural heritage of the Canary Islands: current situation and proposal for action - Núñez, María Esther; Ortiz Repiso, Virginia (Revista General de Información y Documentación, 2019)
The results obtained in a study carried out between the end of 2015 and the beginning of2017 on the state of the heritage of the Canary Islands digitized and accessible through the Internetare presented, with a view to proposing a future regional digital library in the field of semantic webtechnologies. The 87 existing projects are analyzed. Most of them are led by public institutions, butwith a clear disconnection between them. Many initiatives are being carried out, but this workhighlights the shortcomings that exist. These lead to a clear lack of interoperability between thedifferent initiatives, which prevents many of the projects from participating in major collectiveplatforms such as Hispana or Europeana. It is observed that each administration walks, at a generallevel, in its own direction and with its own objectives and approaches, it seems that the digitaldissemination of its heritage should be more a reflection of its own administrative structure than of the very idiosyncrasy of the heritage published on the network. Solutions are proposed to alleviatethese deficiencies and to make a regional digital library of the Canary Islands adapted to othernational and international uses a reality.
Keywords: Cultural heritage; Digital libraries; Digital collections; Canary Islands; Evaluation